Improving Students’ Listening Skills Through Podcasts in the Eighth Grade at SMP Negeri 1 Bua Ponrang - Dian Reskiasari Pratiwi; Reski Yusrini Islamiah Yunus; Andi Mangnguntungi Sudirman (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
This classroom action research investigated the use of English podcasts to improve the listening skills of eighth-grade students at SMP Negeri 1 Bua Ponrang. The participants were 28 students from one eighth-grade class in the 2023/2024 academic year. The study followed the Kemmis and McTaggart action-research cycle of planning, action, observation, and reflection and was conducted in two cycles. Data were collected through a 20-item fill-in-the-blank listening test administered as a diagnostic test, a Cycle I test, and a Cycle II test. The mean score increased from 40.18 in the diagnostic test to 67.86 in Cycle I and 77.68 in Cycle II, representing an overall gain of 37.50 points. Based on the individual scores, the proportion of students reaching the minimum mastery criterion of 75 increased from 10.7% in the diagnostic test to 39.3% in Cycle I and 71.4% in Cycle II. Reflection after Cycle I showed that students had difficulty following lengthy recordings and relatively rapid native-speaker delivery. Cycle II therefore used shorter materials, slower and clearer speech, bilingual explanation, vocabulary preparation, transcripts, songs, games, and repeated listening. Classroom observations indicated that students became more attentive, active, and willing to respond. The findings suggest that podcasts can support listening improvement when their topics, length, delivery speed, scaffolding, and classroom activities are adapted to learners’ proficiency and interests.